Informal and paid care for Brazilian older adults (National Health Survey, 2013) - Maria Fernanda Lima-Costa; Sérgio Viana Peixoto; Deborah Carvalho Malta; Célia Landmann Szwarcwald; Juliana Vaz de Melo Mambrini
ABSTRACT OBJECTIVE To describe the prevalence and sociodemographic factors associated with informal and paid care for Brazilian older adults with functional limitations. METHODS Of the 23,815 participants of the National Health Survey aged 60 or older, 5,978 reported needing help to perform activities of daily living and were included in this analysis. The dependent variable was the source of care, categorized as exclusively informal (unpaid), exclusively formal (paid), mixed or none. The socio-demographic variables were age (60-64, 65-74, ≥ 75 years old), gender and number of residents in the household (1, 2, ≥ 3). The multivariate analysis was based on binomial and multinomial logistic regressions. RESULTS Informal care predominated (81.8%), followed by paid (5.8%) or mixed (6.8%) and no care (5.7%). The receipt of care from any source increased gradually with the number of residents in a same household, regardless of age and gender (OR = 4.85 and 9.74 for 2 and ≥ 3, respectively). Age was positively associated with receiving any care while the male gender showed a negative association. The number of residents in the household showed the strongest association with informal care (OR = 10.94 for ≥ 3 residents), compared with paid (OR = 5.48) and mixed (OR = 4.16) care. CONCLUSIONS Informal care is the main source of help for community-dwelling older adults with functional limitations. In a context of rapid population aging and decline in family size, the results reinforce the need for policies to support long-term care for older Brazilians.